The Impact of Capital Structure and Sales Growth on the Financial Performance of MSMEs in Medan - Putri Wahyuni (Outline Journal of Economic Studies, 2026)
Purpose: This study investigated the impact of capital structure and sales growth on the financial performance of micro, small, and medium enterprises in Medan City. Methods: The researchers utilized a quantitative approach with a causal-associative design. The study selected a sample of thirty business enterprises using purposive sampling criteria based on operational duration and the availability of financial records. The researchers extracted quantitative financial data from the annual reports of the selected enterprises. The data analysis involved classical assumption tests and multiple linear regression models. Results: The regression analysis revealed that capital structure negatively and significantly affected financial performance. Conversely, sales growth positively and significantly impacted financial performance. The statistical model accounted for approximately fifty percent of the variance in the financial performance of the enterprises. Conclusions: The study concluded that excessive reliance on debt diminished profitability due to high interest burdens, whereas robust sales expansion enhanced financial health through economies of scale. Originality/value: This research provided empirical value by demonstrating that enterprise owners must prioritize internal funding and sales optimization over aggressive short-term borrowing to ensure sustainable financial stability in emerging local markets.